Sending a Bit More Coin Home? An Analysis of Retail User Protection in Bitcoin Remittance Markets - Cotton, Jared (Victoria University of Wellington Law Review, 2013)
This article examines the use of Bitcoin in money remittance markets as a specific illustration of wider emerging regulatory issues relating to the use of cryptocurrencies. While there are many conceivable benefits of using Bitcoin for remittances, there are also many risks for users of these remittance services. This article adopts a user perspective to look at what the major concerns are and what existing protections may be available to persons using cryptocurrencies under New Zealand law through the example of using Bitcoin for remittance purposes. The article then summarises approaches taken by other jurisdictions before suggesting a specific regulatory approach to cryptocurrencies that New Zealand should consider adopting.